The Effect of Work Motivation on Employees’ Performance Mediated by Job Satisfaction at Pt. Bank Rakyat Indonesia TBK Rengat Branch Office (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study was to analyze the effect of work motivation on job satisfaction, work motivation on employees’ performance and job satisfaction on employees’ performance and the effect of work motivation on employees’ performance mediated by job satisfaction at PT. Bank Rakyat Indonesia (Persero) Tbk Rengat Branch Office. The data were collected by a close questionnaire. The samples were 65 organic employees working at PT. Bank Rakyat Indonesia (Persero) Tbk Rengat Branch Office. These samples were chosen by saturated sampling technique. Then, the data were analyzed by applying SEM (Structural Equation Modeling) analysis which was operated through SmartPLS 3 Application. The results of this study indicated that: (1) Work motivation has a positive and significant effect on employees’ job satisfaction. (2) Work motivation has a positive and significant effect on employees’ performance. (3) Job satisfaction has a positive and significant effect on employees’ performance. (4) Job satisfaction mediates the influence of work motivations on employees’ performance positively and significantly.